Retirement and loneliness - Sophie Guthmuller; Dörte Heger; Johannes Hollenbach; Anna Werbeck (RWI - Leibniz-Institut für Wirtschaftsforschung, 2023)
We investigate the short- and long-term effects of retirement on loneliness using panel data from the Survey of Health, Aging, and Retirement in Europe. To estimate causal effects, we exploit differences in retirement eligibility rules across and within countries and use retirement thresholds in an instrumental variable setting. On average, we find that entering retirement leads to a significant reduction in loneliness in the long run, although our results show no clear effect in the short run. The reduction is driven by individuals being less likely to feel socially isolated and lacking companionship. Our results suggest that individuals adapt to retirement by increasing their activity levels and reap the benefits in terms of reduced loneliness and social isolation. Heterogeneity analysis by gender reveals that retirement increases feelings of loneliness for women in the short term, and that this effect appears to be driven by women lacking companionship when their partner is not yet retired. – – Wir untersuchen die Auswirkungen von Renteneintritt auf Einsamkeit in der kurzen und langen Frist mit Hilfe von Fragebogendaten der Survey of Health, Aging, and Retirement in Europe. Um einen kausalen Zusammenhang aufzuzeigen, nutzen wir die Unterschiede in den Altersgrenzen der Rentenberechtigungsregelungen zwischen und innerhalb der Länder in einer Instrumentenvariablenschätzung. Kurzfristig zeigen unsere Analysen keine Auswirkungen. Langfristig reduziert der Renteneintritt aber das Einsamkeitsgefühl, da sich die Menschen weniger sozial isoliert fühlen und weniger enge Kontakte vermissen. Unsere Ergebnisse legen nahe, dass Menschen nach einer gewissen Zeit im Ruhestand ihr Aktivitätsniveau erhöhen, was Einsamkeit und sozialer Isolation entgegenwirkt. Unsere geschlechtsspezifische Analyse zeigt allerdings, dass Frauen sich nach Renteneintritt kurzfristig einsamer fühlen und enge Kontakte vermissen, wenn ihr Partner zu dem Zeitpunkt noch nicht im Ruhestand ist.
Keywords: J26; J14; I10; 330; Loneliness; social isolation; retirement; instrumental variable; causal effect